Long‐term Impact of Hearing Aid Provision or Cochlear Implantation on Hearing Handicap. (2nd November 2020) - Kim, Alexander S.; Betz, Joshua F.; Nieman, Carrie L.; Hoyer, Matthew R.; Applebaum, Jeremy; Lin, Frank R.; Goman, Adele M.
Abstract : Objectives/Hypothesis: Previous research has shown hearing handicap to be reduced following hearing aid use or cochlear implantation in short‐to‐medium follow‐up periods, yet the impact of interventions for hearing loss on hearing handicap in the long term remains understudied. This article reports hearing handicap at 6 months, 12 months, and 5 years after either hearing aid provision or cochlear implantation. Study Design: Observational study. Methods: A study of 115 participants from the Studying Multiple Outcomes after Aural Rehabilitative Treatment (SMART) study cohort assessed self‐reported hearing handicap using the Hearing Handicap Inventory for the Elderly Screening version (HHIE‐S) at baseline, 6 months, 12 months, and 5 years. Generalized estimating equations (GEE) were used to estimate the population mean HHIE‐S score over time, accounting for the correlated nature of repeated measures data, and multiple imputation with chained equations was performed to impute missing data. Results: Compared to baseline, mean HHIE‐S scores after hearing aid provision were significantly reduced at 6 months (mean = −7.96, 95% confidence interval [CI]: −10.40, −5.53), 12 months (mean = −6.58, 95% CI: −9.26, −3.90), and 5 years (mean = −4.58, 95% CI: −7.87, −1.30). After cochlear implantation, mean hearing handicap scores were also significantly lower compared to baseline at 6 months (mean = −8.18, 95% CI: −11.07, −5.30), 12 months (mean = −10.04, 95% CI: −12.92, −7.16), and 5 years (mean = −8.97, 95% CI: −12.92, −7.16). Conclusions: This study found short‐term benefits from hearing aids and cochlear implantation on hearing handicap were maintained over 5 years. Laryngoscope, 131:1122–1126, 2021